2021
DOI: 10.1002/ldr.3919
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities as indicators of soil health under a continuous cropping system

Abstract: With growing global interest in the improvement of soil quality and the adoption of sustainable land management systems, there is an urgent need to find early indicators to monitor and manage sustainable soil health. Meta‐analyses provide useful information on microbial communities and community‐level molecular characteristics, which can be exploited as ‘biomarker’ indicators of ecosystem processes for soil health evaluation. Lanzhou lily (Lilium davidii var. unicolor) is the only type of sweet edible lily in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…3b). Our nding was similar to the results from the Lanzhou lily continuous cropping system, where the microbial community compositions were distinguished into three groups during 9 years of continuously replanting [44]: one group (0-3 years), second group (3-6 years), and third group (6-9 years). In addition, a similar result was gained in the monoculture system of soybean [3].…”
Section: Continuous Reduces Microbial Diversity and Populationssupporting
confidence: 88%
“…3b). Our nding was similar to the results from the Lanzhou lily continuous cropping system, where the microbial community compositions were distinguished into three groups during 9 years of continuously replanting [44]: one group (0-3 years), second group (3-6 years), and third group (6-9 years). In addition, a similar result was gained in the monoculture system of soybean [3].…”
Section: Continuous Reduces Microbial Diversity and Populationssupporting
confidence: 88%
“…In soil with rice-wheat rotation fertilized with straw, bacterial community diversity was significantly negatively correlated with pH [38]. Our previous study showed that soil pH increased during the 0-9 years of the Lanzhou lily cropping system, and soil salinization occurred [39], while the organic content and bacterial richness increased due to the continuous application of organic fertilizers to the soil, solving the lily CRPs under the traditional soil management in this lily production area [15]. Therefore, we concluded that the bacterial community structure in the soil significantly changed mainly due to silicon fertilizer and microbial agents, which prevented an increase in pH and a decrease in organic content.…”
Section: Relationship Between Soil Bacteria and Soil Environmentmentioning
confidence: 99%
“…Soil bacteria play an important role in nutrient uptake, resistance to soil-borne diseases, and the activation of the plant defense system against pathogens [12][13][14]. We used NGS technology to analyze the bacterial structures in the rhizosphere of the Lanzhou lily under continuous cropping, and we found that the phylum Proteobacteria and the related genus Sphingomonas can be regarded as biomarkers in the system of lily transplantation [15]. Currently, there are many reports showing the role of microbial agents in regulating soil microbial community, but fewer reports focus on the effects of silicon fertilizer on soil microbial community.…”
Section: Introductionmentioning
confidence: 99%
“…unicolor ), an important economic crop, is the only edible sweet lily in China. It is an endemic species that is only suitable at the altitude of 2000–2600 m, resulting in a narrow distribution in Gansu Province, western China 1 . Bulbs of the L. davidii var .…”
Section: Introductionmentioning
confidence: 99%